MODEL HUBUNGAN LINGKUNGAN EKSTERNAL-KEWIRAUSAHAAN- KINERJA : KASUS DI USAHATANI TEMBAKAU - Priyanto, Sony Heru (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
Few study have been made of how farmers' entrepreneurship affects his farm result. Factors that constructed entrepreneurship also haven't explored by researcher very much. This study aims to know relationship model beetwen external environment-entrepreneurship-farm performance at tobacco industry.This research will be conducted by multilevel analysis with Structural Equation Model to know causal relationship between environment factors such as economics, natural resources, institutions and organization, individual background, entrepreneurship, and farm performance. For cross sectional data in 2003 obtained for 4 Kabupaten which are dominan producers tobaco in Central Java, multilevel model with relationship amongexternal environment, entrepreneurship, found to be adequate representation of the data to estimate farm performance.The empirical result indicate factors like personal aspect together with physical, economic and institutional environment effect farmers' entrepreneurship, which personal aspect to become dominan factor determine entrepreneurship and farm performance. This study also show farmers' entrepreneurship effect with farmer outcome farm performance. Economic structure such as agriculture, Farmers' group or associated, goverment policy and cigareth company supported, also determine level of entrepreneurship and farm performance.The next study, this model can implement in the other field such as the small and medium enterprise and other companies. To test goodness of fit the model, this model can research in the cross cultural context and cross national context, both cross sectional data and longitudinal data .